ETIKA BIROKRASI DALAM PEMBUATAN E-KTP PADA DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN PINRANG - Yuniar, Alfira; Malik, Ihyani; Tahir, Nurbiah (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2024)
This research aims to determine the ethics in e-KTP making services at the Pinrang Regency Population and Civil Registration Service Office. This research uses a research method with a qualitative approach using data obtained through observation, interviews and documentation at the Pinrang Regency Population and Civil Registration Office. This research was conducted for approximately 2 months. It is hoped that the results of the research will provide an in-depth understanding of ethics in e-KTP making services at the Pinrang Regency Population and Civil Registration Service Office in terms of 4 (four) aspects of research observation which include efficiency, impersonal, personal system, responsibility. It is hoped that this research can be used as input for government officials in efforts to improve bureaucratic ethics in serving the community and provide a contribution of knowledge for future researchers.